2019
DOI: 10.1021/acsaem.9b00180
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of Functionalized Carbon Paper Electrodes and Their Correlation to the Fermi Level Derived from Raman Spectra

Abstract: Carbon paper electrodes are employed for different electrochemical applications such as flow batteries and fuel cells. However, redox reactions such as VO2+/VO2 + in a vanadium redox flow battery have been found to possess relatively slow kinetics, resulting in significant activation losses during operation. In this work, we demonstrate a facile and scalable method for nitrogen doping of carbon paper electrodes, leading to superior electrocatalytic activity. The effects of pyrolytic pretreatments under differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 82 publications
3
36
0
Order By: Relevance
“…The Raman spectral mapping of the fresh heat-treated carbon paper (Figure 5a), shows that a higher I D /I G ratio was present on the fibers compared to the graphitic regions (made up of the carbonized binder), due to the more amorphous structure of the carbon fibers. [3] This variation between the graphitic and fiber regions has also been observed for untreated carbon paper. [3] Raman spectral mapping for 100-cycle degraded positive electrode (Figure 5b, where red color in the spectrum of colors indicates high structural defect intensity and blue color indicates lower defect intensity) indicates an increase in the I D /I G ratio compared to the fresh heat-treated carbon paper, suggesting an increase in lattice defects due to chargeÀ discharge cycling operation at the positive side.…”
Section: Raman Spectroscopysupporting
confidence: 57%
See 2 more Smart Citations
“…The Raman spectral mapping of the fresh heat-treated carbon paper (Figure 5a), shows that a higher I D /I G ratio was present on the fibers compared to the graphitic regions (made up of the carbonized binder), due to the more amorphous structure of the carbon fibers. [3] This variation between the graphitic and fiber regions has also been observed for untreated carbon paper. [3] Raman spectral mapping for 100-cycle degraded positive electrode (Figure 5b, where red color in the spectrum of colors indicates high structural defect intensity and blue color indicates lower defect intensity) indicates an increase in the I D /I G ratio compared to the fresh heat-treated carbon paper, suggesting an increase in lattice defects due to chargeÀ discharge cycling operation at the positive side.…”
Section: Raman Spectroscopysupporting
confidence: 57%
“…[3] This variation between the graphitic and fiber regions has also been observed for untreated carbon paper. [3] Raman spectral mapping for 100-cycle degraded positive electrode (Figure 5b, where red color in the spectrum of colors indicates high structural defect intensity and blue color indicates lower defect intensity) indicates an increase in the I D /I G ratio compared to the fresh heat-treated carbon paper, suggesting an increase in lattice defects due to chargeÀ discharge cycling operation at the positive side. The Raman spectral mapping of the 100-cycle degraded negative electrode (Figure 5c) showed a reduction in overall defect distribution of I D /I G compared to heat-treated and positive electrodes.…”
Section: Raman Spectroscopysupporting
confidence: 57%
See 1 more Smart Citation
“…The nitrogen atoms created more defect edges and promoted wettability of electrospun nanofibres, and hence improved its performance towards electron and mass transfer. A common method of improving the performance of carbon electrodes for VRFBs is to heat-treat them in air to add oxygen functionality; though this increases the wettable surface area, it has recently been suggested by Singh et al [137] that nitrogen doping of carbons can have a catalytic effect for the V redox couples, beyond that of simply increasing the surface area with oxygen treatment. They found that though their N-doped carbon papers had an electrochemical surface area (ECSA) 16 times less than that of oxygen treated papers, there was superior catalytic activity towards the VO 2+ /VO2 + couple for the former, meaning N-doping of materials for RFBs electrodes should be further pursued in order to advance the state-of-the-art from the simple air/heat treatments most widely applied in the literature (for example, as outlined in an early work from Sun and Skyllas-Kazacos [138]).…”
Section: Catalysts Additives and Surface Functional Groupsmentioning
confidence: 99%
“…The rationale of selecting CFP was its high electrical conductivity, large surface area, high chemical stability and good mechanical strength. 8 The CFP electrode exhibited randomly oriented microfibers with carbon-based functional groups (e.g., conjugated C=C, C-C, C-OH, and COOH). In depth structural characterization via scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy are shown in Supplementary Information (Supplementary Fig.…”
Section: Electrocatalytic Reduction Of Antraquinone For Biocatalytic Oxyfunctionalizationmentioning
confidence: 99%